Analisis Tingkat Kepuasan Pelanggan Perusahaan Daerah Air Minum Kabupaten Majalengka - Herdiana, Deni; Sulaksana, Jaka (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
The purpose of this study was to determine the level of community satisfaction with PDAM Majalengka Regency and to determine the service quality of PDAM Majalengka Regency. Measurement of the Community Satisfaction Index and the quality of PDAM Majalengka Regency public services is carried out by distributing questionnaires to PDAM customers. The sampling method used is incidental sampling, namely determining the sample by